Secondary metabolites from Lansium domesticum as potential anti-inflammatory iNOS inhibitors: An in silico study - Yadi Oktariansyah; Laila Hanum; Muhammad Habiburrahman (Universitas Islam Negeri Sumatera Utara, 2025)
Inflammation is a crucial mechanism by which the immune system combats disease. However, when it becomes uncontrolled, it can result in acute inflammatory disorders. Although non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for treatment, their associated side effects have prompted the search for safer, natural alternatives. One of the enzymes central to the progression of acute inflammation is inducible nitric oxide synthase (iNOS), particularly its active site, plays a key role in the progression of acute inflammation. Lansium domesticum Corrêa, 1807 have been reported to contain secondary metabolites with anti-inflammatory potential, but their interaction with iNOS has not been systematically explored. This study is the first to comprehensively evaluate these secondary metabolites against iNOS using an in silico approach combing biological activity prediction, physicochemical and pharmacokinetic profiling, and molecular docking simulations. From 53 screened metabolites, nine compounds met drug-likeness and pharmacokinetic criteria and were further analyzed through molecular docking. Ellagic Acid, (+)-Spathulenol, α-Cadinene, and τ-Muurolol showed substantial binding affinities at the iNOS active site, which suggests that they could be good anti-inflammatory agents. These results establish a basis for subsequent in vitro and in vivo validation aimed at creating safe, natural iNOS inhibitors as herbal-based for the alternative anti-inflammatory medicines.